Adherence to the Mediterranean diet and allergic diseases in Korean adults: KNHANES 2013–2016 - Tan, Kaiyue; Sun, Nanren; Chen, Jiaojiao; Long, Jiaqi; Feng, Wenzhe; Zhang, Xiaojie; Tan, Zhimin (Frontiers in Nutrition, 2025)
BackgroundThe prevalence of allergic diseases [e.g., asthma, allergic rhinitis (AR), atopic dermatitis (AD)] has increased significantly in recent years, which is coincides with a shift in modern eating habits. The Mediterranean diet, due to its anti-inflammatory properties, may be beneficial in the prevention of allergic diseases. However, its effects on allergic diseases have not been sufficiently studied. We investigated the relationship between adherence to the Mediterranean diet and allergic diseases.MethodsThis study analyzed the relationship between adherence to the Mediterranean diet (using the modified Mediterranean diet score, mMED) and atopic dermatitis, asthma, and allergic rhinitis in 12,080 participants using data from the 2013–2016 Korean National Health and Nutrition Examination Survey (KNHANES). Multiple logistic regression analyses were used to control for confounding factors such as age, gender, education level, income, and lifestyle.ResultsIn multivariable adjusted models, participants with higher mMED had a significantly lower risk of developing AD (OR 0.57; 95% CI, 0.36–0.92; p trend = 0.0201). When stratified by sex, this risk reduction was more significant in females (OR 0.50; 95% CI, 0.27–0.96; p trend <0.05). Across mMED components, fish and peanut intake were negatively associated with the occurrence of AD and AR (OR 0.55; 95% CI, 0.40–0.76; p trend <0.05, OR 0.75; 95% CI, 0.65–0.87; p trend <0.05). There was no significant association between asthma and AR and mMED scores.ConclusionHigh adherence to the Mediterranean diet is associated with a lower prevalence of atopic dermatitis, especially in women. Fish and peanut intake have an important protective role against atopic diseases.